1996
DOI: 10.1002/hep.510230539
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipopolysaccharide antagonizes transforming growth factor β1-induced apoptosis in primary cultures of hepatocytes

Abstract: Incubation of primary cultures of fetal hepatocytes with lipopolysaccharide (LPS) elicited the expression of nitric oxide (NO) synthetase as well as antagonized the apoptotic cell death evoked by treating the cells with transforming growth factor beta 1 (TGF-beta 1). In addition to LPS, exposure of the cells to chemical NO donors also protected against apoptotic cell death when assayed at concentrations in the low micromolar range. Treatment of hepatocytes with large concentrations of NO donors promoted both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…GSNO was synthesized from glutathione and NaNO 2 following a previous protocol [14]. GSNO was precipitated with acetone and purified after extensive washing with diethylether.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GSNO was synthesized from glutathione and NaNO 2 following a previous protocol [14]. GSNO was precipitated with acetone and purified after extensive washing with diethylether.…”
Section: Methodsmentioning
confidence: 99%
“…GSNO was precipitated with acetone and purified after extensive washing with diethylether. After vacuum drying, an aliquot was characterized by UV spectroscopy [14]. NO release was measured by the accumulation of nitrite and nitrate in the culture medium as previously described using Griess reagent [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…26), we tested the hypothesis that NO regulates apoptosis through nitrosylation of cysteine at the active site of caspase-3-like proteases. We utilized hepatocytes for these studies because we (27)(28)(29) and others (30,31) have shown that NO is hepatoprotective. In addition, hepatocytes express iNOS under a diverse array of conditions associated with cell death and turnover (reviewed in Ref.…”
mentioning
confidence: 99%
“…Indeed, it has been reported that NO plays a dual role, favoring cell viability or inducing apoptotic death depending on the cell type and amount of NO produced (11)(12)(13)(14)(15). For example, moderate NO synthesis inhibits basal apoptosis in B lymphocytes (16,17) or the TGF-␤-induced apoptosis in hepatocytes (18).…”
mentioning
confidence: 99%